When and why does relative leader-member exchange enhance service performance?: The roles of self-efficacy, team commitment, and multifoci team-level differentiation. Issue 7 (8th July 2019) - Yoon, Mahn Hee; Yoon, David J.
Abstract : Purpose: This paper aims to examine the mediating roles of self-efficacy and team commitment in linking service employees' relative leader-member exchange (RLMX) with customer service behaviors and also the moderating roles of team-level differentiations in leader-member exchange (LMX) and team-member exchange (TMX) in influencing these mediation processes. Design/methodology/approach: Data were collected from 467 customer-contact employees working in hotel restaurants. Hierarchical linear modeling analysis was used to test the mediation hypotheses, and moderated path was used to assess the moderated mediation. Findings: Self-efficacy and team-commitment both mediated the relationship between RLMX and customer service behaviors. The differentiations in LMX and TMX significantly interacted with RLMX in predicting self-efficacy and team commitment and also moderated the indirect effects of RLMX on customer service behaviors. Research limitations/implications: Future studies need to incorporate customers' or immediate supervisors' ratings of subordinates' customer service behaviors and replicate the findings in different countries and work settings. Practical implications: Hospitality managers should foster a work environment wherein they develop equal quality relationships with their subordinates in a workgroup and promote high-quality relationships among subordinates in the workgroup to improve subordinates' self-efficacy, team commitment and, subsequently, their customer service behaviors. Originality/value: This study incorporates both self-efficacy and team commitment as motivation-based and social exchange-based mediators, respectively, in predicting customer service behavior. It also extends the boundary condition for the mediations by considering the team-level differentiations in both vertical exchange (LMX) and horizontal exchange (TMX).